Efektifitas Terapi Massage dengan Terapi Mandi Air Hangat terhadap Penurunan Insomnia Lansia - Triyandini,; Asrin,; Upoyo, Arif Setyo (Jurusan Keperawatan FIKES UNSOED, 2010)
Insomnia is one of sleep disturbance which often suffered in old people. Degradation of body system function of old people influence the body stimulation of drug, so that handling of insomnia by non pharmacologic more suggest. One of the non pharmacologic therapy to reduce insomnia scale was massage therapy and warm water bath therapy. The aim of the research was to know the effectiveness of massage therapy and warm water bath therapy to reduce insomnia scale for old people in Panti Wredha Catur Nugraha Banyumas. Research conducted by using quasi experiment method with two group comparation pretest and posttest static design to 12 respondents that fulfilling of inclusive criterion. Sample divided into two group, that was 6 respondents for massage therapy and 6 respondents for warm water bath therapy. Purposive sampling method was used to select determine sample in this study. Insomnia scale was measured by using Pittsburgh Insomnia Rating Scale. In this study, the statistical test was measured by using ï¿½tï¿½ independent test. The result showed that there is significant differences between massage therapy and warm water bath therapy to reduce insomnia scale of old people in Panti Wredha Catur Nugraha Banyumas. While if seem from the p value = 0,000 it means less than . So that refused Null Hipotesis means there were different effectiveness between massage therapy and warm water bath therapy to reduce insomnia scale for old people in Panti Wredha Catur Nugraha Banyumas. The conclusion of this research was that there are different effectiveness between massage therapy and warm water bath therapy to reduce insomnia scale for old people in Panti Wredha Catur Nugraha Banyumas.